Millennial grits on professional accounting profession in a Malaysian setting / Mohd Adha Ibrahim, Nurul Nazlia Jamil and Mohamad Yazis Ali Basah - Ibrahim, Mohd Adha; Jamil, Nurul Nazlia; Ali Basah, Mohamad Yazis (UiTM Cawangan Johor, 2019)
The purpose of this paper is to study how the accounting students’ grit level would affect their intention to become professional accountants. The research was conducted using a questionnaire survey structured with two independent variables namely consistency of interest and perseverance of effort and translated into 17 statements which was then distributed to accounting students at four different universities in the Klang Valley. In total, 153 usable responses were received. The analysis shows that all predictor variables explain about 6.5 per cent of the variability of students’ intention to become professional accountants. Further analysis also shows that one independent variable, namely perseverance of effort has direct significant relationship with a student’s intention to become professional accountant.